Reversal of Direct Oral Anticoagulants: Current Status and Future Directions - Weitz, Jeffrey I. (Seminars in Respiratory and Critical Care Medicine, 2017)
Direct oral anticoagulants (DOACs) are increasingly used for prevention and treatment of venous thromboembolism and for prevention of stroke in patients with nonvalvular atrial fibrillation. In phase III clinical trials that included more than 100,000 patients, the DOACs were at least as effective as vitamin K antagonists (VKAs) and were associated with less serious bleeding, particularly less intracranial bleeding. Real-world evidence supports these outcomes. Despite this, some physicians and patients are concerned about serious bleeding or emergencies unless specific reversal agents for the DOACs are available. However, in clinical trials performed without reversal agents, the outcome of major bleeds was similar or better in patients receiving DOACs than in those taking VKAs. Because of their short half-lives, supportive measures are sufficient to manage most bleeds in patients receiving DOACs. Anticoagulant reversal should only be considered with life-threatening bleeds, with bleeds that fail to respond to usual measures and in patients requiring urgent surgery. Idarucizumab is licensed for dabigatran reversal and andexanet alfa is likely to be soon licensed for reversal of rivaroxaban, apixaban, and edoxaban. To ensure responsible use of these agents, every hospital needs a bleeding management algorithm that identifies patients eligible for reversal and outlines appropriate dosing regimens.
Keywords: andexanet; apixaban; bleeding management; ciraparantag; dabigatran; direct oral anticoagulants; edoxaban; idarucizumab; rivaroxaban